2017
DOI: 10.1039/c7gc00923b
|View full text |Cite
|
Sign up to set email alerts
|

A Schiff base-modified silver catalyst for efficient fixation of CO2 as carboxylic acid at ambient pressure

Abstract: A Schiff base-modified silver catalyst was developed for the direct carboxylation of terminal alkynes with CO2, enabling the efficient synthesis of valuable alkynyl carboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 42 publications
5
37
0
Order By: Relevance
“…CO 2 in presence of two equivalents of Cs 2 CO 3 . A non‐negligible yield of 33 % was obtained ( Table , entry 1 ) in line with previous results showing that the reaction proceeds to some extent under very mild conditions even in the absence of a catalyst . We found that, on increasing the temperature to 60 °C and then to 80 °C the yield increases up to 99 % with a yield of isolated product of 91 % ( Table , entries 2 and 3 , Figure S1 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…CO 2 in presence of two equivalents of Cs 2 CO 3 . A non‐negligible yield of 33 % was obtained ( Table , entry 1 ) in line with previous results showing that the reaction proceeds to some extent under very mild conditions even in the absence of a catalyst . We found that, on increasing the temperature to 60 °C and then to 80 °C the yield increases up to 99 % with a yield of isolated product of 91 % ( Table , entries 2 and 3 , Figure S1 ).…”
Section: Resultssupporting
confidence: 90%
“…A non-negligible yield of 33 % was obtained ( Table 1, entry 1) in line with previous results showing that the reaction proceeds to some extent under very mild conditions even in the absence of a catalyst. [24] We found that, on increasing Supporting information for this article is available on the WWW under https://doi.org/10.1002/hlca.201900258 the temperature to 60°C and then to 80°C the yield increases up to 99 % with a yield of isolated product of 91 % ( Table 1, entries 2 and 3, Figure S1). The increase in yield with temperature is attributed to the increased solubility of the base in DMSO with temperature, and to faster deprotonation kinetics.…”
Section: Resultsmentioning
confidence: 96%
“…With a view to developing at industrial scale C-H carboxylation reactions the use of active heterogeneous catalysts is highly desirable to allow easy catalyst recovery from the reaction mixture and subsequent recycle. However supported metal catalysts are often affected by unsatisfactory activity [152]. Recent advances in the field have been reported by Huang and coworkers by using a Shiff base-modified silver catalyst (169, Scheme 77b) employed in conjuction with Cs 2 CO 3 to carboxylate terminal alkynes (167) to alkynyl carboxylic acids (168, Scheme 77a) [152] in high yields (86-98%) at ambient pressure.…”
Section: C-h Carboxylation With Co 2 Via Heterogeneous Catalysismentioning
confidence: 99%
“…However supported metal catalysts are often affected by unsatisfactory activity [152]. Recent advances in the field have been reported by Huang and coworkers by using a Shiff base-modified silver catalyst (169, Scheme 77b) employed in conjuction with Cs 2 CO 3 to carboxylate terminal alkynes (167) to alkynyl carboxylic acids (168, Scheme 77a) [152] in high yields (86-98%) at ambient pressure. The robust and green catalyst 169 was obtained by deposition of silver nanoparticles (NPs) on the solid support by direct reduction of AgNO3 with a metastable aminal under ultrasonic conditions.…”
Section: C-h Carboxylation With Co 2 Via Heterogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation